2004
DOI: 10.1017/s0031182003004189
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high levels of congenital transmission of Toxoplasma gondii in natural urban populations of Mus domesticus

Abstract: The relative importance of different transmission routes of Toxoplasma gondii has been a matter for debate. This ubiquitous parasite is generally thought to be transmitted by infective oocysts excreted by the definitive host, the cat. Ingestion of undercooked meat has also been considered an important route of transmission in many mammals while congenital transmission has generally been considered relatively rare. Experimental studies demonstrate the ability of T. gondii to be transmitted congenitally, but few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 14 publications
3
60
1
4
Order By: Relevance
“…over several generations) is still to be established. Similar high levels of congenital transmission have recently been reported in other mammals (Mus domesticus and Apodemus sylvaticus) (Owen &Trees, 1998 ;Marshall et al 2004). Furthermore, it is well understood that serial vertical transmission of the closely related parasite Neospora caninum occurs in cattle families (Schares et al 1998 ;Davison, Otter & Trees, 1999) and congenital transmission has been demonstrated in sheep (McAllister et al 1996).…”
Section: Discussionsupporting
confidence: 67%
“…over several generations) is still to be established. Similar high levels of congenital transmission have recently been reported in other mammals (Mus domesticus and Apodemus sylvaticus) (Owen &Trees, 1998 ;Marshall et al 2004). Furthermore, it is well understood that serial vertical transmission of the closely related parasite Neospora caninum occurs in cattle families (Schares et al 1998 ;Davison, Otter & Trees, 1999) and congenital transmission has been demonstrated in sheep (McAllister et al 1996).…”
Section: Discussionsupporting
confidence: 67%
“…In rodents, prevalence is generally low (0 -10% [47,46]), which renders comparisons difficult. High seroprevalences have been occasionally reported in brown rats (70% in Italy [48]) and in house mice (59% in rural and sub-urban areas in England [49]). However, these limited data do not permit to draw a clear pattern among environments in rodents.…”
Section: Variations In T Gondii Dynamics Along the Urban-rural-wild mentioning
confidence: 99%
“…Collection of samples and DNA extraction House mice (Mus domesticus) used in this study were captured within domestic dwellings in the Cheetham Hill area of Manchester, UK as part of a pest control programme (Marshall et al 2004), brown rats (Rattus norvegicus) were captured in urban areas of Manchester. Tissue was obtained from lambs (Ovis aries) which were either aborted, dead at birth or died shortly after birth from 2 farms and contained individuals from 3 breeds, Suffolk cross, Charolais and Lleyns as described by Duncanson et al (2001), Williams et al (2005) and Morley et al (2005).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%